INTERVIEW: Knowledge and Terminology Management at the Danish National Board of Social Services - Møller, Margrethe H.; Toft, Birthe; Rosendahl, David (Communication & Language at Work, 2012)
Margrethe H. Møller interviews David Rosendahl (translator/coauthor: Birthe Toft) “We need to do more than simply create classifications” The concept secretariat of the Danish National Board of Social Services carries out terminology and classification work in connection with IT projects, among others, in the field of social services. This work is interesting for several reasons. On the one hand, terminology work obviously contributes to enhanced efficiency and transparency from the points of view of all types of users. On the other hand, some social services professionals are skeptical vis-à-vis the terminology projects because they fear unification and standardization of their professionalism and working procedures in connection with the introduction of new IT systems. And finally, a number of ethical issues have to be taken into consideration when deciding on terminology in the social services field. All in all, target group and communicative aspects become central to the effort. David Rosendahl Terminology consultant at the Danish National Board of Social Services The Danish National Board of Social Services (“Socialstyrelsen”) is an independent subdivision of The Ministry of Social Affairs and Integration. The Board aims to promote new development and initiatives in social services while also supporting and counselling local authorities in providing services to citizens, i.e. children, young people, socially marginalised groups, elderly and disabled.